The role of interleukin-4 and interleukin-5 Th2 cytokines in assessing severity and prognosis of acute pancreatitis - Doklestić Krstina (Serbian Medical Society, 2021)
Introduction/Objective. Acute pancreatitis (AP) is a relatively common disease which in most patients has favorable course. However, in approximately 20% patients, the course of the disease is more severe with high mortality (40–50%). The evaluation of disease severity is now primarily based on protocols that includes clinical, laboratory, and radiographic diagnostic procedures, APACHE II score, Ranson score, CT index, and CT necrosis score. Key cells in the immunopathogenesis of AP are T-lymphocytes, and recent studies indicate the role of Th2 and their effector cytokines: interleukin (IL) -4 and interleukin (IL) -5. The purpose of our study was to determine the potential clinical value of IL-4 and IL-5 as biochemical markers for predicting development of severe, necrotizing form of acute pancreatitis with systemic complication such as systemic inflammatory response syndrome (SIRS). Methods. This prospective study included 240 patients hospitalized at The Clinic for Emergency Surgery of Clinical Center of Serbia as AP. Levels of IL-4 and IL-5 in serum were detected using commercial Bender Med Systems (BMS716FF) kits. Results. IL-4 and IL-5 were statistically significant increased on the second day of hospitalization with maximum values on the third day. In patients with severe AP complicated with necrosis and/or sepsis values were rising all through the seventh day. Conclusion. Levels of IL-4 and IL-5 in peripheral blood correlate with SIRS, Ranson score and clinical outcome in AP patients, therefore these cytokines are potential early biomarkers of disease progression and related complications.